2008
DOI: 10.1002/sia.2643
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemical and nanomechanical alterations in plasma immersion ion implanted PET

Abstract: Poly(ethylene terephthalate) (PET) surface was treated by plasma immersion ion implantation (PIII or PI 3 ) in nitrogen. The treatment conditions like acceleration voltage, ion fluence and fluence rate were varied systematically. The PIII-induced alterations in the surface chemical composition and bonding of the constituent elements were studied by XPS. Nanoindentation and nanoscratch measurements were applied to investigate the related changes in the hardness, elastic modulus and wear resistance. Nitrogen PII… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The effect of exposure to plasma on PET using PIII is similar but the O/C ratio is reduced, compared to plasma treatment without PIII (Kereszturi et al 2008). This reduction in O/C ratio is consistent with the increasing carbonization of the polymer that accompanies energetic bombardment.…”
Section: Surface Structure Of Plasma Prepared Surfacesmentioning
confidence: 91%
“…The effect of exposure to plasma on PET using PIII is similar but the O/C ratio is reduced, compared to plasma treatment without PIII (Kereszturi et al 2008). This reduction in O/C ratio is consistent with the increasing carbonization of the polymer that accompanies energetic bombardment.…”
Section: Surface Structure Of Plasma Prepared Surfacesmentioning
confidence: 91%
“…The DCSBD was designed to be suitable for flat surfaces treatment in particular. The DCSBD electrode system was powered by AC high voltage source which has a frequency (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) kHz and approximately 20 kV peak-to-peak voltage. In the present study, the discharge power is 320 W and it was operated in the air in order obtain a quasi-homogeneous diffuse plasma surface.…”
Section: Plasma Treatmentmentioning
confidence: 99%
“…Whereas higher friction was recorded for PETP after argon plasma treatment [10]. The scratch resistance of PETP indicates improvements due to the effect of nitrogen plasma immersion ion implantation (PIII) [11]. In a related study, it was demonstrated that the benefits on sliding tribological properties strongly depend on the sliding conditions: the lower friction and wear after PIII treatment only occurred at low pv conditions under dry or water-lubricated sliding and not at high pv conditions [6].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the increase in crosslinking after atmospheric plasma treatment resulted in lower friction and wear of PEEK composites , while an argon plasma treatment resulted in higher friction of PET . The effects of nitrogen plasma immersion ion implantation (PIII) for PET were investigated in previous work, indicating better scratch resistance . In a following work, it was demonstrated that the benefits on sliding tribological properties strongly depend on the sliding conditions: the lower friction and wear after PIII treatment only occurred at low pv conditions under dry‐ or water‐lubricated sliding and not at high pv conditions .…”
Section: Introductionmentioning
confidence: 99%